A surface toughened rigid thermal insulation tile composite material and preparation method thereof
The method enhances the mechanical and thermal properties of rigid thermal insulation tiles by optimizing thermal matching and preventing substrate-shell separation, addressing brittleness and erosion issues, thereby improving stability and extending service life.
Patent Information
- Application Number
- CN202411274669.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-12
AI Technical Summary
Rigid thermal insulation tiles used in hypersonic vehicles are inherently brittle, unable to withstand high-speed airflow erosion, and have low damage tolerance, with poor thermal matching between the substrate and surface toughened shell leading to warping, cracking, and separation during high-temperature applications.
A method involving fiber pretreatment, slurry preparation, composite matrix formation, surface toughening, and aerogel impregnation to enhance the thermal insulation and mechanical properties of the tiles, optimizing thermal matching and preventing substrate-shell separation.
The method improves the tiles' stability, reduces maintenance frequency, and extends service life by enhancing mechanical properties and thermal resistance, while maintaining structural integrity.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of thermal insulation tile composite materials, in particular to a surface toughened rigid thermal insulation tile composite material and a preparation method thereof. Background Art
[0002] When a hypersonic vehicle flies at high speed for a long time in the atmosphere, its surface is subjected to severe aerodynamic forces and aerodynamic heat, which poses a great safety hazard. Adding lightweight, high temperature resistant, heat insulating and wave-transparent thermal insulation materials on the surface of the aircraft can effectively prevent external heat from transferring to the inside and ensure the normal operation of internal equipment. Therefore, it is very important to insulate the aircraft. The thermal insulation materials on the outer surface of the aircraft play an extremely important role in its safety and flight stability. In recent years, rigid thermal insulation tiles have gradually become a research hotspot for thermal insulation materials and thermal protection technologies in hypersonic aircraft.
[0003] Rigid insulation tiles are generally lightweight rigid insulation materials with a three-dimensional mesh structure formed by overlapping one or more short-cut fibers. They have high porosity, certain load-bearing capacity, good wave transmission performance and thermal insulation. In addition, rigid insulation tiles can also control the energy transferred from their surface to the inside, thereby effectively ensuring the stability of the external structure of the spacecraft and the safety of the internal equipment when the spacecraft is flying for a long time. The existing method for preparing rigid insulation tiles is to use quartz fiber, alumina fiber, etc. as the main raw materials, and obtain fiber slurry after short-cutting and pulping; the fiber slurry is formed and dried to obtain an insulation tile blank; the insulation tile blank is sintered at a certain temperature to obtain a rigid insulation tile.
[0004] However, rigid thermal insulation tiles are inherently brittle, cannot withstand high-speed airflow erosion, and have low damage tolerance. To compensate for this defect, in the prior art, a high-strength ceramic toughened shell is usually constructed on the surface of the rigid thermal insulation tile to further enhance toughness and strengthen the tile.
[0005] However, the defect of the above method is that there is a problem of thermal matching between the rigid insulation tile substrate and its surface toughened shell. In high-temperature sintering preparation or high-temperature application environment, the degree of thermal deformation of the rigid insulation tile substrate and its surface toughened shell does not match, and the surface toughened shell is prone to warping and deformation, which leads to cracking and separation of the surface toughened shell of the rigid insulation tile and its substrate, poor overall stability, high overall maintenance frequency and maintenance cost, and short service life.
[0006] Therefore, while improving the defects of the rigid insulation tile's inherent brittleness, inability to withstand high-speed airflow erosion, and low damage tolerance, the thermal matching problem between the rigid insulation tile substrate and its surface toughened shell is optimized to avoid the mismatch in the degree of thermal deformation between the rigid insulation tile substrate and its surface toughened shell during high-temperature sintering preparation or high-temperature application environment. The surface toughened shell is prone to warping and deformation, which leads to cracking and separation of the surface toughened shell of the rigid insulation tile and its substrate. This improves the overall stability of the rigid insulation tile, reduces maintenance frequency and maintenance costs, and extends the service life, which has important technical significance. Summary of the invention
[0007] In order to solve the technical problems existing in the prior art, the present invention provides a surface-toughened rigid thermal insulation tile composite material and a preparation method thereof, which can improve the defects of the rigid thermal insulation tile such as the intrinsic brittleness, inability to withstand high-speed airflow erosion, and low damage tolerance, while optimizing the thermal matching problem between the rigid thermal insulation tile substrate and its surface-toughened shell, thereby avoiding the problem that the rigid thermal insulation tile substrate and its surface-toughened shell are mismatched in thermal deformation during high-temperature sintering preparation or high-temperature application environment, and the surface-toughened shell is prone to warping deformation, resulting in cracking and separation of the surface-toughened shell of the rigid thermal insulation tile from its substrate, thereby improving the overall stability of the rigid thermal insulation tile, reducing maintenance frequency and maintenance costs, and extending the service life.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing a surface toughened rigid thermal insulation tile composite material comprises the following steps: fiber pretreatment, slurry preparation, composite matrix preparation, surface toughening, and aerogel impregnation molding.
[0010] The fiber pretreatment method comprises: dipping the alumina fiber into 12-15 times the weight of silica sol, dipping at 35-40° C. for 2-3 hours in a vacuum environment of 0.06-0.08 MPa, transferring the fiber into a constant temperature drying oven, drying the fiber at 85-90° C. for 10-12 hours, transferring the fiber into a calcining furnace, heating the fiber to 330-350° C., keeping the temperature for 1-2 hours, further heating the fiber to 1050-1100° C., keeping the temperature for 1-1.5 hours, and cooling the fiber naturally to prepare the fiber. The intermediate fiber is obtained; then the intermediate fiber is immersed in 10-12 times the weight of the modified sol, immersed at 35-40°C for 1-2h in a vacuum environment of 0.06-0.08MPa, transferred to a constant temperature drying oven, dried at 85-90°C for 10-12h, transferred to a calcining furnace, heated to 1200-1300°C at a heating rate of 3.5-4°C / min, kept warm for 1-1.5h, and cooled naturally to obtain the pretreated fiber.
[0011] In the fiber pretreatment, the mass concentration of silica sol is 25-30wt%;
[0012] The diameter of the alumina fiber is 7-13 μm and the alumina content is 83-88 wt%.
[0013] The preparation method of the modified sol is as follows: adding cerium chloride and neodymium chloride into deionized water, stirring for 20-30 minutes, and then dropping ammonia water with a mass concentration of 27-28wt% under stirring, and controlling the dropping time of the ammonia water to be 50-60 minutes; after the ammonia water is added, ammonium bicarbonate is continuously added, stirring for 10-20 minutes, stirring and heating to 65-70°C, and keeping stirring for 1.5-2 hours to obtain the modified sol.
[0014] In the preparation of the modified sol, the weight ratio of cerium chloride, neodymium chloride, deionized water, ammonia water and ammonium bicarbonate is 20-21:6.2-6.5:110-115:27-28:6-7.
[0015] The method for preparing the slurry is to chop the fused silica glass fiber and the pretreated fiber into short pieces of 0.8-1 cm respectively, and then mix them with boron nitride, polyacrylic acid and deionized water to obtain a first slurry; and chop the fused silica glass fiber and the pretreated fiber into short pieces of 0.2-0.3 cm respectively, and then mix them with boron nitride, polyacrylic acid and deionized water to obtain a second slurry.
[0016] In the prepared slurry, the diameter of the fused silica glass fiber is 8-10 μm, and the silica content is 97-99 wt %;
[0017] In the first slurry, the weight ratio of fused silica glass fiber, pretreated fiber, boron nitride, polyacrylic acid, and deionized water is 55-58:42-45:3-3.3:0.4-0.45:3700-3800;
[0018] In the second slurry, the weight ratio of fused silica glass fiber, pretreated fiber, boron nitride, polyacrylic acid and deionized water is 50-52:48-50:3.8-4:0.35-0.4:2500-2600.
[0019] The method for preparing the composite matrix comprises the following steps: firstly introducing a first slurry into a mold, filtering and molding it, then continuously introducing a second slurry into the mold, filtering and molding it, and obtaining a composite green body; then placing the mold containing the composite green body in a constant temperature drying oven, drying it at 120-130° C. for 30-32 hours, demolding it, and obtaining a preform; then placing the preform in a calcining furnace, controlling the heating rate to be 4-5° C. / min, heating it to 1200-1300° C., and calcining it at the temperature for 3-4 hours, and obtaining a composite matrix containing a base layer and a buffer layer.
[0020] In the preparation of the composite matrix, the first slurry is formed and calcined to form a matrix layer, and the second slurry is formed and calcined to form a buffer layer;
[0021] The weight ratio of the first slurry to the second slurry is 1.1-1.2:1.
[0022] The surface toughening method comprises the following steps: putting terminal hydroxyl polysiloxane, silicon carbide and aluminum oxide into cyclohexane, grinding them uniformly, and obtaining a toughened shell coating; applying the toughened shell coating to the outer surface of one side of the buffer layer of the composite substrate, controlling the penetration depth of the toughened shell coating into the buffer layer of the composite substrate to be 0.5-0.6 mm, and then transferring the coating to a constant temperature drying oven, drying at 65-70° C. for 2-2.5 hours, heating the coating to 110-120° C., and heat-preserving and curing for 3-4 hours, so that the coating forms a surface toughened shell on the surface of the composite substrate, and cooling the coating naturally to obtain a surface toughened composite substrate.
[0023] In the surface toughening, the weight ratio of terminal hydroxyl polysiloxane, silicon carbide, aluminum oxide and cyclohexane is 100:7-8:6-7:72-76.
[0024] The aerogel impregnation molding method comprises: adding a linear phenolic resin into 2.3-2.7 times the weight of anhydrous ethanol, stirring for 40-50 minutes, and then dripping sec-butyl aluminum and methyltrimethoxysilane at the same time under the stirring condition of 350-400 rpm, and controlling the dripping time of sec-butyl aluminum and methyltrimethoxysilane to be 70-90 minutes; after the dripping of sec-butyl aluminum and methyltrimethoxysilane is completed, continuing to drip triethyl boron, and controlling the dripping time of triethyl boron to be 70-90 minutes; After the addition of triethylboron is completed, stirring is continued for 30-40 minutes, and then hexamethylenetetramine is added and stirred evenly to obtain an aerogel impregnation liquid; the surface-toughened composite matrix is completely immersed in the aerogel impregnation liquid, and the impregnation vacuum degree is controlled to be 0.085-0.095MPa. After vacuum impregnation for 1-1.5 hours, it is transferred to a constant temperature drying oven, kept at 90-95°C for 34-36 hours, and then heated to 110-115°C for 28-30 hours to obtain a surface-toughened rigid insulation tile composite material.
[0025] In the aerogel impregnation molding, the weight ratio of linear phenolic resin, sec-butyl aluminum, methyltrimethoxysilane, triethyl boron and hexamethylenetetramine is 60-65:6-7:10-12:3-4:14-15.
[0026] A surface toughened rigid heat-insulating tile composite material is prepared by the above-mentioned preparation method.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The surface toughened rigid thermal insulation tile composite material and the preparation method thereof of the present invention, in the fiber pretreatment step, after using silicon to coat alumina fibers of specific specifications, the intermediate fibers are further treated with cerium / neodymium composite modified sol, and a secondary composite coating is performed on the intermediate fibers to obtain pretreated fibers, which can improve the thermal insulation performance and high temperature stability of the alumina fibers, further improve the thermal insulation performance of the rigid thermal insulation tile composite material, and improve the bonding performance of the alumina fibers with other raw materials. The mechanical properties of the rigid thermal insulation tile composite material are improved, and further the rigid thermal insulation tile composite material is realized. Strengthening and toughening; then in the slurry preparation step, the raw material fibers are chopped to predetermined length specifications, and then the first slurry and the second slurry are respectively prepared; then the first slurry and the second slurry are respectively introduced into the mold for molding and calcining, the first slurry is formed into a matrix layer of the composite matrix through molding and calcining, and the second slurry is formed into a buffer layer of the composite matrix through molding and calcining, and the thermal matching performance of the composite matrix and the subsequent surface toughening shell is optimized according to the subsequent surface toughening shell characteristics; then in the surface toughening step, the toughening shell coating is applied to the outer surface of the buffer layer of the composite matrix on one side, and solidified to form a surface The surface toughened shell is combined with the buffer layer of the composite matrix to optimize the thermal matching performance of the composite matrix and the subsequent surface toughened shell; then in the aerogel impregnation molding step, the aerogel impregnation liquid is prepared by using organic boron, organic aluminum, and organic silicon to synergistically modify the phenolic resin aerogel, and the surface toughened composite matrix is impregnated, dried, and cured to further improve the thermal insulation performance of the rigid insulation tile composite material, improve the mechanical properties and toughness of the rigid insulation tile composite material, and further enhance the stability of the rigid insulation tile composite material in a high temperature environment; the aforementioned technical methods The segments cooperate and work synergistically with each other, which can improve the inherent brittleness of the rigid insulation tile, its inability to withstand high-speed airflow erosion, and its low damage tolerance, while optimizing the thermal matching problem between the rigid insulation tile substrate and its surface toughened shell. This can prevent the mismatch in the degree of thermal deformation between the substrate and its surface toughened shell during high-temperature sintering or high-temperature application environment, and the proneness of warping of the surface toughened shell, which leads to cracking and separation of the surface toughened shell of the rigid insulation tile and its substrate. This improves the overall stability of the rigid insulation tile, reduces maintenance frequency and maintenance costs, and extends the service life.
[0029] (2) The surface toughened rigid thermal insulation tile composite material of the present invention has a compressive strength of 4.9-5.1 MPa, a compressive strength of 4.7-4.8 MPa at 1200°C, a tensile strength in the thickness direction of 1.29-1.34 MPa, and a fracture toughness of 1.05-1.07 MPa·m 1 / 2 , fracture toughness at 1200℃ is 0.99-1.02MPa·m 1 / 2The compression modulus is 271-276MPa, the thermal conductivity is 0.035-0.037W / m·k, the bonding strength between the surface toughened shell and the substrate is 7.6-8.0MPa, and during the preparation process of the surface toughened rigid insulation tile composite material, there is no delamination, cracking or separation between the surface toughened shell and the substrate, and the interface bonding performance between the toughened shell and the substrate is good.
[0030] (3) After 10 temperature cycles (from room temperature to 1300°C), the surface toughened rigid thermal insulation tile composite material of the present invention did not show delamination, cracking or separation between the surface toughened shell and the matrix, and the fracture toughness was 0.93-0.97MPa·m 1 / 2 The bonding strength between the surface toughened shell and the substrate is 6.6-7.1MPa; at the same time, the difference (absolute value) between the heating permanent line change of the toughened shell and the substrate is 0.007-0.009%. The thermal matching between the toughened shell and the substrate is good, and the overall stability of the rigid insulation tile composite material is high.
[0031] (4) The surface-toughened rigid thermal insulation tile composite material of the present invention is resistant to high-speed airflow erosion, can effectively maintain the aerodynamic shape of the hypersonic aircraft, and at the same time withstand the loads of aerodynamic heat, aerodynamic force and vibration coupling. It has a high damage tolerance and effectively realizes the high-reliability application of the rigid thermal insulation tile composite material. DETAILED DESCRIPTION
[0032] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0033] Example 1
[0034] This embodiment provides a method for preparing a surface toughened rigid thermal insulation tile composite material, specifically:
[0035] 1. Fiber pretreatment
[0036] The alumina fiber was immersed in 12 times the weight of silica sol, immersed at 35°C for 2 hours in a vacuum environment of 0.06MPa, transferred to a constant temperature drying oven, dried at 85°C for 10 hours, transferred to a calcining furnace, heated to 330°C, kept warm for 1 hour, then continued to heat up to 1050°C, kept warm for 1 hour, and naturally cooled to obtain an intermediate fiber; then the intermediate fiber was immersed in 10 times the weight of the modified sol, immersed at 35°C for 1 hour in a vacuum environment of 0.06MPa, transferred to a constant temperature drying oven, dried at 85°C for 10 hours, transferred to a calcining furnace, heated to 1200°C at a heating rate of 3.5°C / min, kept warm for 1 hour, and naturally cooled to obtain a pretreated fiber.
[0037] Wherein, the mass concentration of silica sol is 25wt%.
[0038] The diameter of the alumina fiber is 11 μm and the alumina content is 87 wt%.
[0039] The preparation method of the modified sol is as follows: cerium chloride and neodymium chloride are added into deionized water, stirred for 20 minutes, and then ammonia water with a mass concentration of 27wt% is added dropwise with stirring, and the dropping time of the ammonia water is controlled to be 50 minutes; after the ammonia water is added dropwise, ammonium bicarbonate is added, stirred for 10 minutes, and then the temperature is raised to 65°C with stirring, and the temperature is kept stirring for 1.5 hours to obtain the modified sol.
[0040] The weight ratio of cerium chloride, neodymium chloride, deionized water, ammonia water and ammonium bicarbonate is 20:6.2:110:27:6.
[0041] 2. Preparation of slurry
[0042] The fused silica glass fiber and the pretreated fiber were cut into 0.8 cm respectively, and then mixed evenly with boron nitride, polyacrylic acid and deionized water to prepare the first slurry; the fused silica glass fiber and the pretreated fiber were cut into 0.2 cm respectively, and then mixed evenly with boron nitride, polyacrylic acid and deionized water to prepare the second slurry.
[0043] The diameter of the fused silica glass fiber is 9 μm and the silica content is 98 wt %.
[0044] In the first slurry, the weight ratio of fused silica glass fiber, pretreated fiber, boron nitride, polyacrylic acid, and deionized water is 55:42:3:0.4:3700.
[0045] In the second slurry, the weight ratio of fused silica glass fiber, pretreated fiber, boron nitride, polyacrylic acid, and deionized water is 50:48:3.8:0.35:2500.
[0046] 3. Preparation of composite matrix
[0047] First, the first slurry is introduced into the mold, and after suction filtration and forming, the second slurry is continuously introduced into the mold, and pressure filtration is performed to obtain a composite green body; the mold containing the composite green body is then placed in a constant temperature drying oven, dried at 120°C for 30 hours, and demolded to obtain a preform; the preform is then placed in a calcining furnace, the heating rate is controlled to be 4°C / min, the temperature is raised to 1200°C, and the temperature is kept and calcined for 3 hours to obtain a composite matrix containing a base layer and a buffer layer.
[0048] The first slurry is formed into a base layer through molding and calcining, and the second slurry is formed into a buffer layer through molding and calcining.
[0049] The weight ratio of the first slurry to the second slurry is 1.1:1.
[0050] 4. Surface toughening
[0051] Hydroxyl-terminated polysiloxane, silicon carbide and aluminum oxide are put into cyclohexane and ground evenly to obtain a toughened shell coating; the toughened shell coating is applied to the outer surface of one side of the buffer layer of the composite substrate, and the depth of penetration of the toughened shell coating into the buffer layer of the composite substrate is controlled to be 0.5 mm, and then transferred to a constant temperature drying oven, dried at 65°C for 2 hours, heated to 110°C, and kept warm for curing for 3 hours, the coating forms a surface toughened shell on the surface of the composite substrate, and naturally cooled to obtain a surface toughened composite substrate.
[0052] Wherein, the weight ratio of terminal hydroxyl polysiloxane, silicon carbide, aluminum oxide and cyclohexane is 100:7:6:72.
[0053] 5. Aerogel impregnation molding
[0054] The linear phenolic resin was added into 2.3 times the weight of anhydrous ethanol, and after stirring for 40 minutes, sec-butyl aluminum and methyltrimethoxysilane were added at the same time under the stirring condition of 350rpm, and the adding time of sec-butyl aluminum and methyltrimethoxysilane was controlled to be 70 minutes; after the addition of sec-butyl aluminum and methyltrimethoxysilane was completed, triethyl boron was continued to be added, and the adding time of triethyl boron was controlled to be 70 minutes; after the addition of triethyl boron was completed, stirring was continued for 30 minutes, and then hexamethylenetetramine was added and stirred evenly to obtain an aerogel impregnation solution; the surface-toughened composite matrix was completely immersed in the aerogel impregnation solution, and the impregnation vacuum degree was controlled to be 0.085MPa. After vacuum impregnation for 1 hour, it was transferred to a constant temperature drying oven, kept at 90℃ for 34 hours, and then heated to 110℃ for 28 hours to obtain a surface-toughened rigid insulation tile composite material.
[0055] Wherein, the weight ratio of linear phenolic resin, sec-butyl aluminum, methyltrimethoxysilane, triethyl boron and hexamethylenetetramine is 60:6:10:3:14.
[0056] This embodiment also provides a surface-toughened rigid thermal insulation tile composite material, which is prepared using the aforementioned preparation method.
[0057] Example 2
[0058] This embodiment provides a method for preparing a surface toughened rigid thermal insulation tile composite material, specifically:
[0059] 1. Fiber pretreatment
[0060] The alumina fiber was immersed in 13 times the weight of silica sol, immersed in a vacuum environment of 0.07MPa at 38°C for 2.5h, transferred to a constant temperature drying oven, dried at 88°C for 11h, transferred to a calcining furnace, heated to 340°C, kept warm for 1.5h, then continued to heat up to 1080°C, kept warm for 1.2h, and naturally cooled to obtain an intermediate fiber; then the intermediate fiber was immersed in 11 times the weight of the modified sol, immersed in a vacuum environment of 0.07MPa at 38°C for 1.5h, transferred to a constant temperature drying oven, dried at 88°C for 11h, transferred to a calcining furnace, heated to 1250°C at a heating rate of 3.8°C / min, kept warm for 1.2h, and naturally cooled to obtain a pretreated fiber.
[0061] Wherein, the mass concentration of silica sol is 28wt%.
[0062] The diameter of the alumina fiber is 11 μm and the alumina content is 87 wt%.
[0063] The preparation method of the modified sol is as follows: cerium chloride and neodymium chloride are added into deionized water, stirred for 25 minutes, and then ammonia water with a mass concentration of 27.5wt% is added dropwise with stirring, and the ammonia water addition time is controlled to be 55 minutes; after the ammonia water is added dropwise, ammonium bicarbonate is added, stirred for 15 minutes, and then the temperature is raised to 68°C with stirring, and the temperature is kept stirring for 1.8 hours to obtain the modified sol.
[0064] The weight ratio of cerium chloride, neodymium chloride, deionized water, ammonia water and ammonium bicarbonate is 20.5:6.3:112:27.5:6.5.
[0065] 2. Preparation of slurry
[0066] The fused silica glass fiber and the pretreated fiber were cut into 0.9 cm, respectively, and then mixed evenly with boron nitride, polyacrylic acid and deionized water to prepare a first slurry; the fused silica glass fiber and the pretreated fiber were cut into 0.25 cm, respectively, and then mixed evenly with boron nitride, polyacrylic acid and deionized water to prepare a second slurry.
[0067] The diameter of the fused silica glass fiber is 9 μm and the silica content is 98 wt %.
[0068] In the first slurry, the weight ratio of fused silica glass fiber, pretreated fiber, boron nitride, polyacrylic acid, and deionized water is 57:43:3.2:0.43:3750.
[0069] In the second slurry, the weight ratio of fused silica glass fiber, pretreated fiber, boron nitride, polyacrylic acid, and deionized water is 51:49:3.9:0.38:2550.
[0070] 3. Preparation of composite matrix
[0071] First, the first slurry is introduced into the mold, and after filtering and forming, the second slurry is continuously introduced into the mold, and filter-pressed to obtain a composite green body; the mold containing the composite green body is then placed in a constant temperature drying oven, dried at 125°C for 31 hours, and demolded to obtain a preform; the preform is then placed in a calcining furnace, the heating rate is controlled to be 4.5°C / min, the temperature is raised to 1250°C, and the temperature is kept and calcined for 3.5 hours to obtain a composite matrix containing a base layer and a buffer layer.
[0072] The first slurry is formed into a base layer through molding and calcining, and the second slurry is formed into a buffer layer through molding and calcining.
[0073] The weight ratio of the first slurry to the second slurry is 1.15:1.
[0074] 4. Surface toughening
[0075] Hydroxyl-terminated polysiloxane, silicon carbide and aluminum oxide are put into cyclohexane and ground evenly to obtain a toughened shell coating; the toughened shell coating is applied to the outer surface of one side of the buffer layer of the composite substrate, and the depth of the toughened shell coating penetrating into the buffer layer of the composite substrate is controlled to be 0.55 mm, and then transferred to a constant temperature drying oven, dried at 68°C for 2.2 hours, heated to 115°C, and kept warm for curing for 3.5 hours. The coating forms a surface toughened shell on the surface of the composite substrate, and is naturally cooled to obtain a surface toughened composite substrate.
[0076] Wherein, the weight ratio of terminal hydroxyl polysiloxane, silicon carbide, aluminum oxide and cyclohexane is 100:7.5:6.5:75.
[0077] 5. Aerogel impregnation molding
[0078] The linear phenolic resin was added into 2.5 times the weight of anhydrous ethanol, and after stirring for 45 minutes, sec-butyl aluminum and methyltrimethoxysilane were added at the same time under the stirring condition of 380rpm, and the adding time of sec-butyl aluminum and methyltrimethoxysilane was controlled to be 80 minutes; after the addition of sec-butyl aluminum and methyltrimethoxysilane was completed, triethyl boron was continued to be added, and the adding time of triethyl boron was controlled to be 80 minutes; after the addition of triethyl boron was completed, stirring was continued for 35 minutes, and then hexamethylenetetramine was added and stirred evenly to obtain an aerogel impregnation solution; the surface-toughened composite matrix was completely immersed in the aerogel impregnation solution, and the impregnation vacuum degree was controlled to be 0.09MPa. After vacuum impregnation for 1.2 hours, it was transferred to a constant temperature drying oven, kept at 92℃ for 35 hours, and then heated to 112℃ for 29 hours to obtain a surface-toughened rigid insulation tile composite material.
[0079] Wherein, the weight ratio of linear phenolic resin, sec-butyl aluminum, methyltrimethoxysilane, triethyl boron and hexamethylenetetramine is 62:6.5:11:3.5:14.5.
[0080] This embodiment also provides a surface-toughened rigid thermal insulation tile composite material, which is prepared using the aforementioned preparation method.
[0081] Example 3
[0082] This embodiment provides a method for preparing a surface toughened rigid thermal insulation tile composite material, specifically:
[0083] 1. Fiber pretreatment
[0084] The alumina fiber was immersed in 15 times the weight of silica sol, immersed at 40°C for 3 hours in a vacuum environment of 0.08MPa, transferred to a constant temperature drying oven, dried at 90°C for 12 hours, transferred to a calcining furnace, heated to 350°C, kept warm for 2 hours, then continued to heat up to 1100°C, kept warm for 1.5 hours, and naturally cooled to obtain an intermediate fiber; then the intermediate fiber was immersed in 12 times the weight of the modified sol, immersed at 40°C for 2 hours in a vacuum environment of 0.08MPa, transferred to a constant temperature drying oven, dried at 90°C for 12 hours, transferred to a calcining furnace, heated to 1300°C at a heating rate of 4°C / min, kept warm for 1.5 hours, and naturally cooled to obtain a pretreated fiber.
[0085] Wherein, the mass concentration of silica sol is 30wt%.
[0086] The diameter of the alumina fiber is 11 μm and the alumina content is 87 wt%.
[0087] The preparation method of the modified sol is as follows: cerium chloride and neodymium chloride are added into deionized water, stirred for 30 minutes, and then ammonia water with a mass concentration of 28wt% is added dropwise with stirring, and the dropping time of the ammonia water is controlled to be 60 minutes; after the ammonia water is added dropwise, ammonium bicarbonate is added, stirred for 20 minutes, and then the temperature is raised to 70°C with stirring, and the temperature is kept stirring for 2 hours to obtain the modified sol.
[0088] The weight ratio of cerium chloride, neodymium chloride, deionized water, ammonia water and ammonium bicarbonate is 21:6.5:115:28:7.
[0089] 2. Preparation of slurry
[0090] The fused silica glass fiber and the pretreated fiber were cut into 1 cm, respectively, and then mixed evenly with boron nitride, polyacrylic acid and deionized water to prepare the first slurry; the fused silica glass fiber and the pretreated fiber were cut into 0.3 cm, respectively, and then mixed evenly with boron nitride, polyacrylic acid and deionized water to prepare the second slurry.
[0091] The diameter of the fused silica glass fiber is 9 μm and the silica content is 98 wt %.
[0092] In the first slurry, the weight ratio of fused silica glass fiber, pretreated fiber, boron nitride, polyacrylic acid, and deionized water is 58:45:3.3:0.45:3800.
[0093] In the second slurry, the weight ratio of fused silica glass fiber, pretreated fiber, boron nitride, polyacrylic acid, and deionized water is 52:50:4:0.4:2600.
[0094] 3. Preparation of composite matrix
[0095] First, the first slurry is introduced into the mold, and after filtration and forming, the second slurry is continuously introduced into the mold, and filter-pressed to obtain a composite green body; the mold containing the composite green body is then placed in a constant temperature drying oven, dried at 130°C for 32 hours, and demolded to obtain a preform; the preform is then placed in a calcining furnace, the heating rate is controlled to be 5°C / min, the temperature is raised to 1300°C, and the temperature is kept and calcined for 4 hours to obtain a composite matrix containing a base layer and a buffer layer.
[0096] The first slurry is formed into a base layer through molding and calcining, and the second slurry is formed into a buffer layer through molding and calcining.
[0097] The weight ratio of the first slurry to the second slurry is 1.2:1.
[0098] 4. Surface toughening
[0099] Hydroxyl-terminated polysiloxane, silicon carbide and aluminum oxide are put into cyclohexane and ground evenly to obtain a toughened shell coating; the toughened shell coating is applied to the outer surface of one side of the buffer layer of the composite substrate, and the depth of the toughened shell coating penetrating into the buffer layer of the composite substrate is controlled to be 0.6 mm, and then transferred to a constant temperature drying oven, dried at 70°C for 2.5 hours, heated to 120°C, and cured at this temperature for 4 hours, the coating forms a surface toughened shell on the surface of the composite substrate, and naturally cooled to obtain a surface toughened composite substrate.
[0100] Wherein, the weight ratio of terminal hydroxyl polysiloxane, silicon carbide, aluminum oxide and cyclohexane is 100:8:7:76.
[0101] 5. Aerogel impregnation molding
[0102] The linear phenolic resin was added into 2.7 times the weight of anhydrous ethanol, and after stirring for 50 minutes, sec-butyl aluminum and methyltrimethoxysilane were simultaneously added under stirring at 400 rpm, and the adding time of sec-butyl aluminum and methyltrimethoxysilane was controlled to be 90 minutes; after the addition of sec-butyl aluminum and methyltrimethoxysilane was completed, triethyl boron was continued to be added, and the adding time of triethyl boron was controlled to be 90 minutes; after the addition of triethyl boron was completed, stirring was continued for 40 minutes, and then hexamethylenetetramine was added and stirred evenly to obtain an aerogel impregnation solution; the surface-toughened composite matrix was completely immersed in the aerogel impregnation solution, and the impregnation vacuum degree was controlled to be 0.095 MPa. After vacuum impregnation for 1.5 hours, it was transferred to a constant temperature drying oven, kept at 95°C for 36 hours, and then heated to 115°C for 30 hours to obtain a surface-toughened rigid insulation tile composite material.
[0103] Wherein, the weight ratio of linear phenolic resin, sec-butyl aluminum, methyltrimethoxysilane, triethyl boron and hexamethylenetetramine is 65:7:12:4:15.
[0104] This embodiment also provides a surface-toughened rigid thermal insulation tile composite material, which is prepared using the aforementioned preparation method.
[0105] Comparative Example 1
[0106] The technical solution of Example 2 is adopted, but the difference is that in the fiber pretreatment step, the use of the modified sol is omitted, and the intermediate fiber is used as the pretreated fiber in the subsequent steps.
[0107] Comparative Example 2
[0108] The technical solution of Example 2 is adopted, but the differences are: 1) in the fiber pretreatment step, the addition of neodymium chloride is omitted in the preparation of the modified sol; 2) in the aerogel impregnation molding step, the addition of sec-butylaluminum and triethylboron is omitted.
[0109] The compressive strength, 1200°C compressive strength, thickness direction tensile strength, fracture toughness, 1200°C fracture toughness, compression modulus, thermal conductivity, and bonding strength between the surface toughened shell and the substrate of the surface toughened rigid thermal insulation tile composite materials of Examples 1-3 and Comparative Examples 1-2 were tested respectively; and it was observed whether the surface toughened shell and the substrate had delamination, cracking, or separation problems.
[0110] Among them, the 1200℃ compressive strength is the compressive strength of the surface toughened rigid insulation tile composite material at a temperature of 1200℃; the 1200℃ fracture toughness is the fracture toughness of the surface toughened rigid insulation tile composite material at a temperature of 1000℃, and the fracture toughness and 1200℃ fracture toughness are both tested by the single-edge notched beam method (SENB method).
[0111] The specific results are shown in the following table:
[0112]
[0113] Furthermore, the surface toughened rigid thermal insulation tile composite materials of Examples 1-3 and Comparative Examples 1-2 were placed in a calcining furnace, heated to 1300°C at a heating rate of 30°C / min in an air atmosphere, kept warm for 8 hours, and then naturally cooled to room temperature; the aforementioned heating-natural cooling process was taken as one temperature change cycle, and was performed continuously for 10 times to observe whether the surface toughened shell and the matrix had delamination, cracking, and separation problems, and to detect the fracture toughness and the bonding strength of the surface toughened shell and the matrix of each rigid thermal insulation tile composite material; at the same time, the length measuring instrument method was used to detect the heating permanent line change of the surface toughened shell and the matrix, and the difference between the heating permanent line change of the toughened shell and the matrix was calculated. Among them, the difference is the heating permanent line change value of the toughened shell minus the heating permanent line change value of the matrix, and the absolute value is taken.
[0114] The specific results are shown in the following table:
[0115]
[0116] It can be seen that the preparation method of the surface toughened rigid thermal insulation tile composite material of the present invention, in the fiber pretreatment step, after using silicon to coat alumina fibers of specific specifications, continues to use cerium / neodymium composite modified sol to treat the intermediate fibers, and performs secondary composite coating on them to obtain pretreated fibers, which can improve the thermal insulation performance and high-temperature stability of the alumina fibers, further improve the thermal insulation performance of the rigid thermal insulation tile composite material, and improve the bonding performance of the alumina fibers with other raw materials. The mechanical properties of the rigid thermal insulation tile composite material are improved, and further realize the rigid thermal insulation tile composite material. Strengthening and toughening; then in the slurry preparation step, the raw material fibers are chopped to predetermined length specifications, and then the first slurry and the second slurry are respectively prepared; then the first slurry and the second slurry are respectively introduced into the mold for molding and calcining, the first slurry is formed into a matrix layer of the composite matrix through molding and calcining, and the second slurry is formed into a buffer layer of the composite matrix through molding and calcining, and the thermal matching performance of the composite matrix and the subsequent surface toughening shell is optimized according to the subsequent surface toughening shell characteristics; then in the surface toughening step, the toughening shell coating is applied to the outer surface of the buffer layer of the composite matrix on one side, and solidified to form a surface The surface toughened shell is combined with the buffer layer of the composite matrix to optimize the thermal matching performance of the composite matrix and the subsequent surface toughened shell; then in the aerogel impregnation molding step, the aerogel impregnation liquid is prepared by using organic boron, organic aluminum, and organic silicon to synergistically modify the phenolic resin aerogel, and the surface toughened composite matrix is impregnated, dried, and cured to further improve the thermal insulation performance of the rigid insulation tile composite material, improve the mechanical properties and toughness of the rigid insulation tile composite material, and further enhance the stability of the rigid insulation tile composite material in a high temperature environment; the aforementioned technical methods The segments cooperate and work synergistically with each other, which can improve the inherent brittleness of the rigid insulation tile, its inability to withstand high-speed airflow erosion, and its low damage tolerance, while optimizing the thermal matching problem between the rigid insulation tile substrate and its surface toughened shell. This can prevent the mismatch in the degree of thermal deformation between the substrate and its surface toughened shell during high-temperature sintering or high-temperature application environment, and the proneness of warping of the surface toughened shell, which leads to cracking and separation of the surface toughened shell of the rigid insulation tile and its substrate. This improves the overall stability of the rigid insulation tile, reduces maintenance frequency and maintenance costs, and extends the service life.
[0117] Unless otherwise specified, all percentages used in the present invention are by mass.
[0118] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a surface toughened rigid thermal insulation tile composite material, characterized in that: The method comprises the following steps: fiber pretreatment, slurry preparation, composite matrix preparation, surface toughening, and aerogel impregnation molding; The fiber pretreatment method comprises: impregnating alumina fiber into silica sol, vacuum impregnating and drying, calcining, and obtaining intermediate fiber; impregnating the intermediate fiber into modified sol, vacuum impregnating and drying, transferring the intermediate fiber into a calcining furnace, heating the fiber to 1200-1300° C., and keeping the temperature to obtain pretreated fiber; The preparation method of the modified sol is as follows: adding cerium chloride and neodymium chloride into deionized water, stirring evenly, and then dropping ammonia water into the deionized water under stirring; after the ammonia water is added, adding ammonium bicarbonate, stirring evenly, heating to 65-70° C., keeping the temperature and stirring, to obtain the modified sol; The method for preparing the slurry is: chopping the fused silica glass fiber and the pretreated fiber into 0.8-1 cm respectively, and then mixing them with boron nitride, polyacrylic acid, and deionized water to obtain a first slurry; chopping the fused silica glass fiber and the pretreated fiber into 0.2-0.3 cm respectively, and then mixing them with boron nitride, polyacrylic acid, and deionized water to obtain a second slurry; The method for preparing the composite matrix comprises: introducing a first slurry into a mold, filtering and molding, and then continuously introducing a second slurry into the mold, filtering and molding to obtain a composite green body; the composite green body is dried, demoulded, and calcined to obtain a composite matrix containing a base layer and a buffer layer; The surface toughening method comprises: adding terminal hydroxyl polysiloxane, silicon carbide and aluminum oxide into cyclohexane, grinding them evenly, and obtaining a toughened shell coating; applying the toughened shell coating to the outer surface of the buffer layer of the composite substrate, drying, heating and curing, and obtaining a surface toughened composite substrate; The aerogel impregnation molding method comprises the following steps: impregnating a surface toughened composite matrix with aerogel, drying the matrix, and curing the matrix by heating to obtain a surface toughened rigid thermal insulation tile composite material.
2. The method for preparing the surface toughened rigid thermal insulation tile composite material according to claim 1, characterized in that: In the fiber pretreatment, the weight ratio of alumina fiber to silica sol is 1:12-15; The mass concentration of silica sol is 25-30wt%; The diameter of alumina fibers is 7-13 μm, and the alumina content is 83-88 wt%; The weight ratio of the intermediate fiber to the modified sol is 1:10-12; The heating rate to 1200-1300°C is 3.5-4°C / min.
3. The method for preparing the surface toughened rigid thermal insulation tile composite material according to claim 1, characterized in that: In the fiber pretreatment, the mass concentration of ammonia water used in the preparation of the modified sol is 27-28wt%; Control the ammonia addition time to 50-60min; The weight ratio of cerium chloride, neodymium chloride, deionized water, ammonia water and ammonium bicarbonate is 20-21: 6.2-6.5:110-115:27-28:6-7。 4. The method for preparing the surface toughened rigid thermal insulation tile composite material according to claim 1, characterized in that: In the prepared slurry, the diameter of the fused silica glass fiber is 8-10 μm, and the silica content is 97-99 wt %; In the first slurry, the weight ratio of fused silica glass fiber, pretreated fiber, boron nitride, polyacrylic acid, and deionized water is 55-58:42-45:3-3.3:0.4-0.45:3700-3800; In the second slurry, the weight ratio of fused silica glass fiber, pretreated fiber, boron nitride, polyacrylic acid and deionized water is 50-52:48-50:3.8-4:0.35-0.4:2500-2600.
5. The method for preparing the surface toughened rigid thermal insulation tile composite material according to claim 1, characterized in that: In the preparation of the composite matrix, the drying temperature is 120-130° C. and the drying time is 30-32 hours; The calcination temperature is 1200-1300°C; The calcination heating rate is 4-5℃ / min; The calcination time at 1200-1300℃ is 3-4h.
6. The method for preparing the surface toughened rigid thermal insulation tile composite material according to claim 1, characterized in that: In the preparation of the composite matrix, the first slurry is formed and calcined to form a matrix layer, and the second slurry is formed and calcined to form a buffer layer; The weight ratio of the first slurry to the second slurry is 1.1-1.2:
1.
7. The method for preparing the surface toughened rigid thermal insulation tile composite material according to claim 1, characterized in that: During the surface toughening, the penetration depth of the toughened shell coating into the composite substrate buffer layer is controlled to be 0.5-0.6 mm; The weight ratio of terminal hydroxyl polysiloxane, silicon carbide, aluminum oxide and cyclohexane is 100:7-8:6-7:72-76.
8. The method for preparing the surface toughened rigid thermal insulation tile composite material according to claim 1, characterized in that: The aerogel impregnation molding method comprises the following steps: adding a linear phenolic resin into anhydrous ethanol, stirring evenly, and then dripping sec-butyl aluminum and methyltrimethoxysilane at the same time under a stirring condition of 350-400 rpm; after dripping sec-butyl aluminum and methyltrimethoxysilane, continuing to drip triethyl boron; after dripping triethyl boron, stirring, and then adding hexamethylenetetramine, stirring evenly, to obtain an aerogel impregnation liquid; completely impregnating a surface-toughened composite substrate into the aerogel impregnation liquid, and after vacuum impregnation, transferring the substrate into a constant temperature drying oven, keeping the substrate at 90-95° C. for 34-36 hours, and then heating the substrate to 110-115° C. for 28-30 hours, to obtain a surface-toughened rigid thermal insulation tile composite material.
9. The method for preparing the surface toughened rigid thermal insulation tile composite material according to claim 8, characterized in that: In the aerogel impregnation molding, the weight ratio of the linear phenolic resin to anhydrous ethanol is 1:2.3-2.7; Control the dropping time of sec-butyl aluminum and methyltrimethoxysilane to 70-90 min; Control the dripping time of triethylborane to be 70-90min; The weight ratio of linear phenolic resin, sec-butyl aluminum, methyltrimethoxysilane, triethyl boron and hexamethylenetetramine is 60-65:6-7:10-12:3-4:14-15.
10. A surface toughened rigid thermal insulation tile composite material, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.
